Hydrogen production via glycerol dry reforming over fibrous Ni/KCC-1 - Nornasuha, Abdullah; Nurul Aini, Mohamed Razali; Herma Dina, Setiabudi; Chin, Sim Yee; Aishah, Abdul Jalil; Abdul Rahman, Mohamed (Elsevier Ltd, 2023)
The research intended to evaluate the catalytic activity of Ni-doped on KCC-1 to produce hydrogen thru the reforming process of glycerol and CO2 (GDR). A hydrothermal microemulsion approach was applied to synthesize mesoporous silica KCC-1, which was then impregnated with 10 wt% Ni using an ultrasonic-assisted impregnation technique. XRD, BET, and FTIR were used to analyze the physicochemical characteristics of KCC-1 and Ni loaded on KCC-1. A stainless-steel vertical reactor fixed with a catalyst bed inside was used to run the GDR process at 800 °C, Patm, and a 1:1 ratio of glycerol to CO2. KCC-1 exposed sphere fibrous feature bordered with dendritic fibre observed by TEM with a 268 m2/g in specific surface area and 200–400 nm in particle size. The Ni/KCC-1 catalyst achieved 45.25 %, 33.71 %, and 65.64 % glycerol conversion and syngas (H2 and CO) yields, respectively. The high catalytic performance was credited to the fibre-like structure of KCC-1, which facilitates the access of bulky mass glycerol and CO2 to the Ni active species. Thus, this finding has proven that the exceptional structure of the support material could promise catalytic performance in various applications, particularly glycerol dry reforming.